2013
DOI: 10.1055/s-0033-1333877
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fat Grafting in the Treatment of Posttraumatic Maxillofacial Deformities

Abstract: The first autologous adipose tissue grafting was performed in 1893 with an open approach by a German surgeon named Neuber, 1 who successfully managed an orbitopalpebral scar secondary to tubercular osteomyelitis with fat harvested from the arm.In early 1980s Illouz introduced liposuction performed by a syringe and Fournier introduced liposuction performed by a suction pump. 2-5 They described a closed technique of unpurified fat injection that was called "lipofilling." The inconsistent results of their work ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Although multiple procedures are usually required, the procedures are minimally invasive and hospitalization is short. We also found that sedation and local anesthesia can be sufficient when transplanting fat into the head and neck area, as has been described in prior studies [ 6 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although multiple procedures are usually required, the procedures are minimally invasive and hospitalization is short. We also found that sedation and local anesthesia can be sufficient when transplanting fat into the head and neck area, as has been described in prior studies [ 6 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 80%
“…A study by Arcuri et al investigated 19 patients who underwent posttraumatic reconstruction of maxillofacial deformities with fat transplantation. They achieved excellent results with adequate facial balance after clinical and software analysis [ 6 ]. We treated a 44-year-old patient, who had suffered a gunshot wound to the face two decades ago, resulting in enucleation of the right eye and the need for reconstruction of the right lower eyelid with a paramedian forehead flap.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Currently, little and contradictory information is available regarding the impact of the surgery-first approach and traditional approach on patients' psychological status and quality-of-life outcomes. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Therefore, the aims of this study were to assess the personality traits of orthognathic patients and to investigate and compare the changes related to psychosocial well-being, self-esteem, anxiety, and quality of life between presurgical and postsurgical phases in patients undergoing traditional and surgery-first orthognathic treatments.…”
mentioning
confidence: 99%
“…2 , 9 11 The design of a new small blunt cannula, the fat centrifugation, has become the Coleman technique, an elective therapy of many craniofacial deformities. 12 In recent years, maxillofacial and craniofacial applications have been reported and described: localized tissue atrophy, tissue loss after trauma, post-tumor resection, congenital complex craniofacial deformities, burns, and hemifacial asymmetry (eg, Romberg syndrome, scleroderma). 12 16 Recent studies have shown that human adipose tissue represents a rich source of adipose stem cells, featuring secretion of angiogenic and anti-apoptotic factors in animals.…”
mentioning
confidence: 99%
“… 12 In recent years, maxillofacial and craniofacial applications have been reported and described: localized tissue atrophy, tissue loss after trauma, post-tumor resection, congenital complex craniofacial deformities, burns, and hemifacial asymmetry (eg, Romberg syndrome, scleroderma). 12 16 Recent studies have shown that human adipose tissue represents a rich source of adipose stem cells, featuring secretion of angiogenic and anti-apoptotic factors in animals. 17 , 18 Some authors have reported the differentiation of adipose-derived cells into chondrocytes, myocytes, osteoblasts, and, most recently, neural progenitor cells.…”
mentioning
confidence: 99%